Forfatningsdokumenter fra Danmar, Norge og Sverige 1809-1849 - Riis, Thomas, 1966-; Loebert, Sönke; Michalsen, Dag; Isberg, Magnus, 1939- (Constitutions of the World from the late 18th century to the middle of the 19th century. Europe ;, 2008)
The book edition of Constitutions of the World from the late 18th Century to the middle of the 19th Century is the most complete and academically thorough collection of its kind. It contains constitutional documents from all over the world, written from 1776 to the end of the year 1849. This collection includes about 1,000 constitutions, human rights declarations, and draughts of constitutions that never came into force, from this period. These early constitutional documents were collected and examined in archives and libraries all over the world, as part of a project by the Deutsche Forschung.